The modeling of studies of literary directions of the early modernism - Nezhyva, Lyudmyla (ScienceRise: Pedagogical Education, 2017)
Methodological complexes of the study of literary direction of the early modernism: impressionism, expressionism, symbolism are modeled in the paper. The content and technologies of the methodical model are conditioned by a style dominant of a literary direction. In impressionism it is impressions, in expressionism – a force of emotional expression, in symbolism – intuition of cognition and artistic representation of the world. The methodological base is the principle of aestheticism. This principle is expressed in the development of aesthetic feeling, connected with an experience of beautiful in art. For impressionists it is beauty of nature that is a source of life energy; symbolists search for an ideal of beauty, opposing the imperfect world to spirituality; expressionists see it in aesthetics of emotions, personal experience manifestation In the process of the aesthetical development of pupils the axiological line of the literary education is realized. The specificity of styles of literry directions conditions the specificity of the method of their study. At lessons on impressionism it is important to compare impressions in literature and painting and to teach pupils to express their impressions aesthetically. In the process of studying impressionism it is necessary to accent the resonance character of artistic presentation of a personal tragedy that may be realized using Ukrainian poetic cinematograph. The necessary condition of symbolism study is an activation of pupils’ intuition, using which they may approach to the understanding of ambiguous abstract images-symbols